GREEN HYDROGEN ENERGY USING PBBR2 UNDER ELECTROCHEMICAL WATER SPLITTING - Tom, Deepa Rosh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Green route hydrogen extracted from renewable energy sources through the splitting of water is an emerging and promising energy carrier for the upcoming years, and industries like steel production and chemical manufacturing, like ammonia, are exploring green hydrogen. Lead Bromide perovskites are known for high absorption coefficients, excellent charge transport, optical application, etc, and doped lead bromide perovskites are efficient to use as catalysts for the production of green hydrogen. The electrodes doped with-PbBr₂/NF reinforced the conductivity, and their nanosheet structure, which offers a large surface area for catalytic activity, are the most promising electrocatalysts for HER compared to pure PbBr₂/NF, especially in an alkaline medium, because of its outstanding catalytic activity, excellent stability, and simple production method. The parameter, low onset potential and low overpotential, makes the electrodes efficient electro-catalysts for HER.